2018
DOI: 10.1103/physreve.97.040601
|View full text |Cite
|
Sign up to set email alerts
|

Glass transition of soft colloids

Abstract: We explore the glassy dynamics of soft colloids using microgels and charged particles interacting by steric and screened Coulomb interactions, respectively. In the supercooled regime, the structural relaxation time τ_{α} of both systems grows steeply with volume fraction, reminiscent of the behavior of colloidal hard spheres. Computer simulations confirm that the growth of τ_{α} on approaching the glass transition is independent of particle softness. By contrast, softness becomes relevant at very large packing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
101
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 51 publications
21
101
1
Order By: Relevance
“…The states at lower temperatures were obtained by cooling the higher temperature states at constant pressure. The points on the curves correspond to the scaled distances at which the proper integrals of the radial density lead to the coordination numbers 1,2,3,4,5,6,7,8,9,10,15,20,25,30,40,50,60,70,80,90,100,120,140,160,180,200. Note that in the lower temperature glass states, i.e., at T ≤ 0.002 there develops an additional small peak at (r/a) ≈ 2.67.…”
Section: Pair Distribution Functions (Pdfs)mentioning
confidence: 99%
“…The states at lower temperatures were obtained by cooling the higher temperature states at constant pressure. The points on the curves correspond to the scaled distances at which the proper integrals of the radial density lead to the coordination numbers 1,2,3,4,5,6,7,8,9,10,15,20,25,30,40,50,60,70,80,90,100,120,140,160,180,200. Note that in the lower temperature glass states, i.e., at T ≤ 0.002 there develops an additional small peak at (r/a) ≈ 2.67.…”
Section: Pair Distribution Functions (Pdfs)mentioning
confidence: 99%
“…Thus, some have argued that the softness does not dominate the fragility of colloidal glasses. Instead, it was suggested that other mechanisms relying on the the microscopic details of the soft colloids are important for the drastic change in the fragility in the previous experiments [37,50,51]. Here, we elucidate the effect of the softness on the fragility of soft colloids in order to resolve the conflicting interpretations.…”
Section: Introductionmentioning
confidence: 84%
“…This finding was used to suggest that softer potentials should result in strong glasses [35]. However, the drastic variations in m k have not been reproduced in previous simulations by modification of the softness of the potential alone [37,[47][48][49]. For instance, Philippe et al, considered the soft particles interacting via the Hertz potential V H (r) = H (1 − r/σ) 2 Θ(r − σ), where Θ(x) is the Heaviside step function, and σ is the diameter of the particles [37].…”
Section: Stiffness Of the Dlvo Potential And Dramatic Fragility Changesmentioning
confidence: 96%
See 2 more Smart Citations